Cutaneous kinase activity correlates with treatment outcomes following PI3K delta inhibition in mice with experimental pemphigoid diseases - Ghorbanalipoor, Saeedeh; Emtenani, Shirin; Parker, Melissa; Kamaguchi, Mayumi; Osterloh, Colin; Pigors, Manuela; Gross, Natalie; Khil’chenko, Stanislav; Kasprick, Anika; Patzelt, Sabrina; Wortmann, Diana; Ibrahim, Ibrahim O.; et al. (Frontiers in Immunology, 2022)
Chronic blistering at the skin and/or mucous membranes, accompanied by a varying degree of inflammation, is the clinical hallmark of pemphigoid diseases that impose a major medical burden. Pemphigoid diseases are caused by autoantibodies targeting structural proteins of the epithelial basement membrane. One major pathogenic pathway of skin blistering and inflammation is activation of myeloid cells following Fc gamma receptor-dependent binding to the skin-bound immune complexes. This process requires activation of specific kinases, such as PI3K, which have emerged as potential targets for the treatment of pemphigoid diseases. Yet, it is unknown if global cutaneous kinase activity present in lesional pemphigoid disease correlates with therapeutic effects following treatment with a given target-selective kinase inhibitor. To address this, we here first determined the kinase activity in three different mouse models of pemphigoid diseases: Antibody transfer-induced mucous membrane pemphigoid (MMP), antibody transfer-induced epidermolysis bullosa acquisita (EBA) and immunization-induced EBA. Interestingly, the kinome signatures were different among the three models. More specifically, PI3K was within the kinome activation network of antibody transfer-induced MMP and immunization-induced EBA, but not in antibody transfer-induced EBA. Next, the therapeutic impact of the PI3K-selective inhibitor parsaclisib was evaluated in the three model systems. In line with the kinome signatures, parsaclisib had therapeutic effects in antibody transfer-induced MMP and immunization-induced EBA, but not in autoantibody-induced EBA. In conclusion, kinase activation signatures of inflamed skin, herein exemplified by pemphigoid diseases, correlate with the therapeutic outcomes following kinase inhibition, demonstrated here by the PI3K inhibitor parsaclisib.